Investigación de diversos factores que influyen en la salud mental percibida en la participación en actividades físicas en Sumatra Occidental, Indonesia: un enfoque que utiliza SEM-PLS (Investigating various factors that influence perceived mental health in physical activity participation in West Sumatera, Indonesia: An approach using SEM-PLS): Factors that affect the Mental Health of sports Participants - Sepdanius, Endang; Bin Mohd Sidi, M. Adli; Binti Sanuddin, Nurul Diyana; Afriani , Rini; Orhan, Bekir; Mario , Deby (Retos, 2024)
Problem Statement. Individual involvement in physical activity or sports is significant for the survival of a healthy and quality life, so the supporting and influencing factors need to be investigated. Purpose. This study aims to test a model related to factors that influence perceptions of mental health, including cognitive awareness, emotions, spirituality, and social environment for sports participants. Methods. A total of 1,351 volunteers from 18 regions in West Sumatra participated in this study. The data collection technique used a survey via Google Forms, distributed via WhatsApp social media. Data were analyzed using the Partial Least Square (PLS) method by assessing content validity, Average Variance Extracted (AVE), Inner Model, and hypothesis testing. Result. The results showed that cognitive awareness significantly affects awareness of the social environment (t = 13.142; P